The Effect of Perceived Empowering Leader Behaviors on Employee Voice in Technical and Vocational Training Organization of Guilan Province - Mohammad sadegh Hassanzadeh; Razieh Bagherzadeh Khodashahri; Ehsan Ekradi (Allameh Tabataba'i University Press, 2016)
This study aims to investigate the effects of perceived empowering leader behaviors on employee voice.The aim of the current research is practical and the data collection method is descriptive and correlational which has been gathered by the questionnaires ("the employee voice" questionnaire of Van Dyne and LePine and "empowering leadership" questionnaire of Arnold et al.,)and survey required data. The research included all employees in Technical and Vocational Training Organization of Guilan province, 459 employees were considered as statistical population and 210 people were chosen as sample by simple classified sampling method (Quota) and Corcoran formula. face validity of the questionnaire, convergent validity and reliability was confirmed. The statistical research results have been studied using Smart PLS2 and SPSS 20. The research findings indicate that perceived empowering leader behaviors has a significant impact on employee voice(498/0 β= )) 96/1 (t> .Moreover, participative decision making and coaching dimensions of empowering leader behaviors have a significant impact(399/0β=) و(753/0 β=) on employee voice but informing dimension of empowering leader behaviors don't have a significant impact(96/1>t>96/1- ) on employee voice.